One year weekly dynamics of limnological conditions and phytoplankton in Lake Bonilla, Costa Rica - Umaña Villalobos, Gerardo (2016)
The detailed response of tropical lake phytoplankton to weather variations has been little studied, but it seems that composition varies in response to rain and wind variability over the course of the year. In order to gather more evidence on this variation, the weekly variability of phytoplankton composition was studied in Lake Bonilla, a low land (380 masl) 30 m deep tropical lake, from April 2010 to May 2011. Temperature variation at several depths was recorded automatically, and measurements of dissolved oxygen, water transparency, and nutrients were performed several times during the study period. The lake showed a warm monomictic pattern, with deep mixing occurring during the hemispherical winter, especially after a heavy rain period in December 2010. Phytoplankton was dominated by a few species: a colonial Cyanobacteria (Aphanocapsa sp., functional group F) and two colonial Chlorococcaceae (Botryococcus braunii and Eutetramorus tetrasporus, both in the functional group K). Their relative dominance shifted throughout the year, following changes in water column conditions in response to weather variations. Although changes in main functional groups indicate a shift in resource availability rather than energy, it was clear that attention should also be given to particular species adaptations beyond those used for establishing functional groups.